Consequenses of Molotov-Ribbentrop pacts from independent Lithuania from the internationl law view - A. Loeber, Dietrich (Genocidas ir rezistencija, 2025)
The implications of the Molotov–Ribbentrop Pact have not been completely eradicated even today. The lingering question of the continuity of Lithuanian statehood is one of the consequences of the Pact. Unfortunately, one circumstance greatly weakens Lithuania’s international status and hinders its foreign policy. This circumstance is directly related to the legal implications of the Pact, namely the continuity of Lithuania’s independence. In other words, the question is whether Lithuania is in fact continuing the statehood it had before the Second World War. This question concerns, for example, signed treaties, state assets and debts... So, the question of the continuity of Lithuania’s statehood will remain an ‘unresolved’ question until Lithuania’s continuity is universally recognised. The consequences of the ‘unresolved’ continuity, and hence the other implications of the Pact, are felt in various spheres. Three of these are: the legal literature, the actions of other states, and Lithuania’s status in international organisations.